2012
DOI: 10.1051/0004-6361/201220420
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide site comparison for submillimetre astronomy

Abstract: Aims. The most important limitation for ground-based submillimetre (submm) astronomy is the broad-band absorption of the total water vapour in the atmosphere above an observation site, often expressed as the precipitable water vapour (PWV). A long-term statistic on the PWV is thus mandatory to characterize the quality of an existing or potential site for observational submm-astronomy. In this study we present a three-year statistic (2008)(2009)(2010) of the PWV for ground-based telescope sites all around the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…The agreement is not as good on days with large PWV values, since large negative biases (GOES/GFS -APEX) are shown. Tremblin et al (2012) also show large negative PWV biases during large PWV episodes in Chajnantor in September 2009 from Infrared Atmospheric Sounding Interferometer (IASI) polar satellite data (see Appendix A in Tremblin et al 2012). On the other hand, Tremblin et al (2011) found larger but positive biases between PWV values obtained from IASI satellite data and ground-based PWV observations at Dome C, in the South Pole.…”
Section: Pwv Estimation From Goes/fnl and Goes/gfs Data At The Apex Sitementioning
confidence: 86%
See 2 more Smart Citations
“…The agreement is not as good on days with large PWV values, since large negative biases (GOES/GFS -APEX) are shown. Tremblin et al (2012) also show large negative PWV biases during large PWV episodes in Chajnantor in September 2009 from Infrared Atmospheric Sounding Interferometer (IASI) polar satellite data (see Appendix A in Tremblin et al 2012). On the other hand, Tremblin et al (2011) found larger but positive biases between PWV values obtained from IASI satellite data and ground-based PWV observations at Dome C, in the South Pole.…”
Section: Pwv Estimation From Goes/fnl and Goes/gfs Data At The Apex Sitementioning
confidence: 86%
“…A number of site testing studies have been conducted to find good places for submillimeter/millimeter astronomy (Peterson et al 2003;Yang et al 2010;Radford et al 2011;Tremblin et al 2011Tremblin et al , 2012, and they have identified Mauna Kea in Hawaii, the Chajnantor plateau in the north of Chile, and some regions in the south pole as very good sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider et al 2009;Tremblin et al 2011;Matsushita et al 1999;Peterson et al 2003) already showed that a few sites are well-suited for submm, mid-IR, and FIR astronomy and their transmission properties are rather well determined (for example by Fourier Transform Spectrometer obervations in the 0.5-1.6 THz range at Mauna Kea/Hawaii (Pardo et al 2001)). The high-altitude ( 5000 m) Chilean sites are known for dry conditions (see Matsushita et al 1999;Peterson et al 2003), and site testing is now carried out at the driest place on Earth, Antarctica (see Chamberlin et al 1997;Yang et al 2010;Tremblin et al 2011). Comparisons between Antarctic and Chilean sites are difficult and uncertain since they rely on ground-based instruments that use different methods and calibration techniques (see Peterson et al 2003, for example).…”
Section: Introductionmentioning
confidence: 99%
“…A meaningful comparison is possible if several independent instruments are used at each place. An example of such a study is the one of Tremblin et al (2011) that obtained transmission data at Dome C thanks to radio-soundings and the radiometers HAMSTRAD (Ricaud et al 2010) and SUMMIT08. However, it is rare to have many instruments at one site.…”
Section: Introductionmentioning
confidence: 99%